Measuring thermal spread during bipolar cauterizing using an experimental pneumoperitoneum and thermal sensors - Siracusano, Salvatore; Marchioro, Giacomo; Scutelnic, Dumitru; Brunelli, Matteo; Talamini, Renato; Porcaro, Antonio Benito; Fiorini, Paolo; Muradore, Riccardo; Daffara, Claudia (Frontiers in Surgery, 2023)
It is well known that robotic surgery requires continous haemostasis to maximize the clean vision of the operating field. During nerve-sparing RARP bipolar electrocoagulation is often used but its use is controversial for the possible thermal damage of neurovascular bundles. We manufactured a sealed plexiglass chamber (SPC) to reproduce experimentally the enviromental conditions of pneumoperitoneum during RARP. In particular we evaluated in 64 pig musculofascial tissues (PMTs) of approximately 3x3x2 cm3 the spatial-temporal thermal distribution in the tissue and the correlation with the electrosurgery-induced tissue damage in a controlled, CO2-rich environment modeling the laparoscopy conditions to assess critical heat spread of bipolar cauterizing used during surgical procedure by the employment of a thermal camera (C2). Bipolar instruments used at 30 W showed a mean thermal spread area of 16 mm² when applied for 2 seconds and 28 mm² when applied for 4 seconds. At 60 W, bipolar instruments showed a mean thermal spread and 22 mm² (C2) when applied for 2 seconds; and 28 mm² (C2) when applied for 4 seconds. Finally, histopathological analysis showed that thermal damage is distributed predominantly on the surface rather than in depth. The application of these results is very interesting both for the definition of an accurate use of bipolar cautery during nerve-sparing RARP and for the development of a new thermal endoscope for robotic use that we designed, patented and recently published.